2015
DOI: 10.3171/2014.11.jns14174
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability in the incidence of carcinomatous meningitis

Abstract: OBJECT The aim of the study was to investigate whether there are seasonal differences in the occurrence of carcinomatous meningitis (CM), with a greater prevalence of the disease in months with higher temperatures. METHODS The authors searched the records of all patients with a diagnosis of CM from 1998 until 2013 at the University Hospital of Patras, Greece. The date of hospitalization was extracted for each patient. The cases were divided into 2 categories depending on the time of CM diagnosis. Based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Another benefit of not including Q2 or Q3 is that seasonal trends in outcomes during winter months have been described for certain conditions, such as subarachnoid hemorrhage and carcinomatous meningitis, which may have otherwise confounded our results. 10,13 All neurosurgical cases in the given time intervals for which residents were members of the neurosurgical team were included in the study. Cases in which residents did not provide surgical assistance were excluded; these cases were defined as those in which "Attending Alone" was indicated for the ATTEND variable or 0 (zero) for the PGY (Postgraduate Year) variable.…”
Section: Methods Study Designmentioning
confidence: 99%
“…Another benefit of not including Q2 or Q3 is that seasonal trends in outcomes during winter months have been described for certain conditions, such as subarachnoid hemorrhage and carcinomatous meningitis, which may have otherwise confounded our results. 10,13 All neurosurgical cases in the given time intervals for which residents were members of the neurosurgical team were included in the study. Cases in which residents did not provide surgical assistance were excluded; these cases were defined as those in which "Attending Alone" was indicated for the ATTEND variable or 0 (zero) for the PGY (Postgraduate Year) variable.…”
Section: Methods Study Designmentioning
confidence: 99%
“…We have previously tested our hypothesis that there is a seasonality in the incidence of carcinomatous meningitis. 1 Although further validation is needed in a larger cohort, we found that leptomeningeal metastasis occurred more often during warm months of the year which, in the case of Greece, is the period generally marked with the larger daytime length. 1 Carcinomatous meningitis is closely related to brain metastasis, and a logical question is whether warm season is marked by a greater propensity also for brain metastasis.…”
Section: Dear Editormentioning
confidence: 67%
“…1 Although further validation is needed in a larger cohort, we found that leptomeningeal metastasis occurred more often during warm months of the year which, in the case of Greece, is the period generally marked with the larger daytime length. 1 Carcinomatous meningitis is closely related to brain metastasis, and a logical question is whether warm season is marked by a greater propensity also for brain metastasis. 2 We conducted a single-center retrospective review of the medical records of patients with brain metastases that received whole brain irradiation from 2008 to 2013 (6 years).…”
Section: Dear Editormentioning
confidence: 67%
“…With the accumulation of greenhouse gases, global warming, and changing meteorological factors, there is an increasing frequency of abnormally hot and cold temperatures, which are the direct expression of climate variability. Although it is not clear whether it is the increased temperature of warm months, carcinomatous meningitis was observed to have a higher incidence in these months . Evidence from more studies is warranted to confirm the causal association.…”
Section: Potential Critical Connections Of Climate Change and Cancer ...mentioning
confidence: 97%
“…Although it is not clear whether it is the increased temperature of warm months, carcinomatous meningitis was observed to have a higher incidence in these months. 14 Evidence from more studies is warranted to confirm the causal association. The direct effects of extreme temperatures like heat waves may worsen the conditions of cancer patients because of their impaired thermoregulation and immune function.…”
Section: Change and Cancer Riskmentioning
confidence: 99%